(3EQTGO GdWGdHjf Edi fgL GdeSJQTOjfs - (3GdSjhQj, GdMdj, GdCSOj, GdebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826(3g`s
(3ChdgG (B:s
(3Ef Chdi eG jUQa ajg bhI aMhd GdCacGQ(B... (3CeG HYO aMQj ef CcQeg Gddg(B... (3hSejJg EQTGO GdWGdHjf Edi fgL GdeSJQTOjf(B...s
(3BNQgG (B:s
(3CYGPfG Gddg hEjGce ef GdcaQ hGdaSb hGdfaGb(B...(3aEfj HGdbUhQ deSQa hGdNWGjG deYJQas
(3JHUQI GdYfhGf (B:s
(3fgL GdeSJQTOjf(B: (3ddMSf Hf jhSa GdMdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3GdCYdGe(B: (3L(B7(3, U(B282s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds